Existência, não existência global de solução e estabilidade assintótica para a equação da onda com memória - Flávio Alexandre Falcão Nascimento (2013)
In this work, we study the existence, the global non-existence and the asymptotic behavior of solutions for the wave equation with memory. First, we deal with the solutions for the following model of the semilinear viscoelastic wave equation with a nonlinear damping term and nonlinear source terms acting on the domain and on the boundary